Transshipment operations optimization of sea-rail intermodal container in seaport rail terminals. (March 2020) - Yan, Baicheng; Zhu, Xiaoning; Lee, Der-Horng; Jin, Jian Gang; Wang, Li
Highlights: The direct-transshipment mode between vessels and trains is underlined. A tailored rolling horizon method could help to solve the problem effectively. The dwell time of containers on trains should be taken into consideration. Increasing the capacity of rail mounted gantry cranes shows more positive effects. Prolonging the time window of trains would be in favor of a better transshipment plan. Abstract: This paper tackles the sea-rail transshipment operation problem of seaport rail terminals, which includes two key sub-problems involved in sea-rail intermodal container transportation, namely train schedule template and transshipment plan of inbound containers. With limited resources and time constraints, operators need to decide the placed-in and taken-out time of trains to coordinate with vessels' unloading time and the transshipment plan of inbound containers (i.e. the amount of containers that are transshipped between different vessels and trains in each time slot) to maximize the number of direct-transshipment containers while minimizing the storage time and dwell time of inbound containers. The problem is formulated as an integer programming model, and a tailored rolling horizon approach with the adaptive horizon and backtracking strategy is proposed. The performance of the algorithm is verified by a set of instances. The results suggest that the handling capacity of rail-mounted gantry cranes shows a more significant effect on the performance of transshipment operation than other factors. The negative effect caused by insufficient handling capacity could be alleviated by methods like prolonging the feasible service time of trains and enhancing the operational capacity of shunting engines.